Positive Leukocyte Esterase Dipstick Test: Association With Spontaneous Bacterial Peritonitis In Patients Suffering From Liver Cirrhosis - Shahzadi, Sumbul; Siddiqi, Fuad Ahmad; Khan, Imran; Siddiqi, Kanaz Ahmad; Khan, Javed Ahmad; Cheema, Ayesha Ashraf (Journal of Rawalpindi Medical College, 2024)
Objective: To assess the diagnosing utility of the leukocyte esterase dipstick test by determining the association of a positive leukocyte esterase dipstick test with spontaneous bacterial peritonitis (SBP) in patients suffering from liver cirrhosis. Methods: This was a cross-sectional study conducted at the Department of Medicine, Combined Military Hospital (CMH), Rawalpindi from January 2023 to December 2023. This study included a total of 65 patients with liver cirrhosis with ascites that fulfilled the exclusion and inclusion criteria. 50 mL of ascitic fluid was drawn from every patient. Afterwards, a dipstick test strip (URS-10A strip) was carefully introduced into each sample. The colour that appeared on the dipstick after 2 minutes was observed and that colour was compared with the colour significance chart mentioned on the dipstick box. Meanwhile, 100ml of the same sample of ascitic fluid was sent to a laboratory for routine evaluation of leucocyte count for the confirmation of diagnosis for SBP. The test results of the two investigations were compared using a Chi-square test. A p-value less than 0.05 was considered to be statistically significant. Results: A total of 65 individuals participated in our study. Out of the total, 39 (60.0%) were male with the mean age of 57.03±9.063, and 26 (40.0%) were females with the mean age of 55.54±8.453. A Chi-square was performed to assess the association between the dipstick test & ascitic fluid routine evaluation results. The Dipstick test was found to have 85.18% sensitivity and 92.11% specificity (p<0.0001). Conclusions: In conclusion, it can be stated that although various studies have reported variations in the positive predictive values (PPV) and sensitivity value, the accurate calculation of negative predictive value (NPV) in the majority of studies affirms the beneficial use of leukocyte esterase test strips in healthcare settings for patients suffering from cirrhosis-related asities with spontaneous bacterial peritonitis.